2021
DOI: 10.1158/1535-7163.mct-20-1105
|View full text |Cite
|
Sign up to set email alerts
|

PAK4-NAMPT Dual Inhibition Sensitizes Pancreatic Neuroendocrine Tumors to Everolimus

Abstract: Metastatic pancreatic neuroendocrine tumors (PNET) remain an unmet clinical problem. Chronologic treatment in PNETs includes observation (watchful protocol), surgery, targeted therapy, and chemotherapy. However, increasing evidence illustrates that the outcomes of targeted therapeutic options for the treatment of advanced PNETs show minimal response. The FDA-approved mTOR inhibitor everolimus does not shrink these tumors. It only delays disease progression in a subset of patients, while a significant fraction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In vitro, KPT-9274 was found to synergize with Everolimus in cell growth inhibition, colony suppression, and glucose uptake. In vivo, the combination of KPT-9274 (150 mg/kg) with Everolimus (2.5 mg/kg) produced a statistically significant suppression in tumor growth, a scenario not observed for single agent of Everolimus (Mpilla et al, 2021). Mechanism study reveals that resistance to Everolimus is mainly due to activation of mTORC2, and treatment with the combination efficaciously resensitizes to BON-1 cell lines (Mpilla et al, 2021).…”
Section: Kpt-9274mentioning
confidence: 92%
“…In vitro, KPT-9274 was found to synergize with Everolimus in cell growth inhibition, colony suppression, and glucose uptake. In vivo, the combination of KPT-9274 (150 mg/kg) with Everolimus (2.5 mg/kg) produced a statistically significant suppression in tumor growth, a scenario not observed for single agent of Everolimus (Mpilla et al, 2021). Mechanism study reveals that resistance to Everolimus is mainly due to activation of mTORC2, and treatment with the combination efficaciously resensitizes to BON-1 cell lines (Mpilla et al, 2021).…”
Section: Kpt-9274mentioning
confidence: 92%
“…The only known drug that targets both NAMPT and PAK4 is KPT-9274, which is the subject of NCT02702492 listed in Table 1 . In this clinical trial, Gabriel et al concluded that KPT-9274 could make pancreatic neuroendocrine tumor cells more sensitive to traditional mTOR inhibitors, resulting in better therapeutic outcomes ( Mpilla et al, 2021 ). KPT-9274 has been demonstrated to modulate Wnt/β-linked protein signaling and decrease the growth of multiple tumor cell lines and subcutaneous xenograft models of mantle cell lymphoma.…”
Section: Nicotinamide Phosphoribosyltransferase Inhibitorsmentioning
confidence: 99%
“…PAK4 and NAMPT are mTOR regulators, which are aberrantly overexpressed in preclinical NET models and lead to everolimus resistance. 44 KPT-9274 is a PAK4-NAMPT dual inhibitor that, when administered at 150 mg/kg with everolimus (2.5 mg/kg), worked synergistically to suppress two pNET-derived xenografts. 44 Enhanced understanding of tumour biology and molecular behaviour of NETs may lead to the development of combinations to overcome tumour resistance mechanisms.…”
Section: Everolimusmentioning
confidence: 99%